The clinician's handbook for dental sleep medicine - Berley, Ken; Carstensen, Stephen ([S.l.] : Quintessence Publishing Co, Inc., 2019)
It has been estimated that 20 million Americans suffer from moderate to severe OSA, and at least one patient in five has mild OSA. The primary treatment prescribed by sleep physicians is CPAP, but patient compliance with this therapy is unacceptably low, between 25% and 50%. There is a significant opportunity for dentists to provide a viable alternative therapy - oral appliance therapy (OAT). OAT results in much better adherence to therapy than CPAP, and while OAT is not as efficacious as CPAP, this increased compliance results in comparable therapeutic results. Currently, a board-certified sleep physician is the only medical professional qualified to diagnose OSA and other sleep-related breathing disorders (SRBDs), so dentists must coordinate with a sleep physician to provide OAT. This book is the how-to guide, a gateway to a successful dental sleep medicine practice. Written by two experts in the field, it clearly delineates the dentist's role in the treatment of SRBDs and gives practical advice on how to incorporate dental sleep medicine into an existing dental practice, as well as how to work with sleep physicians to best support patient care. In addition to step-by-step instructions for examination, appliance selection, and follow-up care, complications of OAT, legal issues, and medical insurance and Medicare considerations are included to fully prepare the dentist for the journey into dental sleep medicine.
The clinician's handbook for dental sleep medicine -- Contents -- Foreword -- Preface -- Chapter 1: Clinical Guide for the Practice of Dental Sleep Medicine -- Chapter 2: An Overview of Sleep & Sleep Disorders -- Chapter 3: Dental Sleep Medicine Protocol and Practice -- Chapter 4: Integrating Dental Sleep Medicine into Your Practice -- Chapter 5: Treatment Decisions and Appliance Selection -- Chapter 6: Delivery of a Custom MAD -- Chapter 7: Complications of Oral Appliance Therapy -- Chapter 8: Evaluating Therapy and Ongoing Care -- Chapter 9: The New Reality -- Chapter 10: Legal Issues Related to the Practice of Dental Sleep Medicine -- Chapter 11: Medical Insurance and Medicare -- Chapter 12: Pediatric Airway Problems -- Sleep Medicine Terminology -- Recommended Materials -- Index.
Includes bibliographical references and index.
Keywords: Sleep Apnea Syndromes -- therapy; Sleep Bruxism -- therapy; Dentistry -- methods